Preparation process of environment-friendly cement raw material grinding-aid grinding agent

By employing a multi-step synergistic chemical modification process, a core-shell structured nanocomposite powder mineralizer was prepared, solving the problem in existing technologies where industrial solid waste is difficult to convert into high-performance cement raw material additives. This process improved the grindability, burnability, and chloride ion penetration resistance of cement raw materials, while also enabling the high-value utilization of solid waste.

CN121342394APending Publication Date: 2026-01-16ZHEJIANG CHANGYING BUILDING MATERIALS TECH CO LTD

Patent Information

Application Number
CN202511615737.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing technologies struggle to transform industrial solid waste into high-performance cement raw material additives through deep chemical modification, particularly in improving the impermeability of marine cement and preventing chloride ion penetration. Furthermore, simple physical mixing or primary chemical reactions are insufficient to meet the demands of high-performance cement materials.

Method used

A multi-step synergistic chemical modification process was adopted, including low-temperature plasma activation of electrolytic manganese slag, RAFT polymerization modification of industrial waste alkaline solution, supramolecular self-assembly and biomimetic silicification, to prepare a core-shell structured nanocomposite powder mineralizer, and the final product was obtained by spray drying.

Benefits of technology

It significantly improves the grindability and burnability of cement raw materials, reduces coal consumption in clinker burning, endows marine cement with excellent resistance to chloride ion penetration, and realizes high-value-added resource utilization of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121342394A_ABST
    Figure CN121342394A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement admixtures, in particular to a preparation process of an environment-friendly cement raw material grinding-aid grinding agent. According to the process, electrolytic manganese residues and industrial waste alkali liquor are used as raw materials, and the core is that multi-step synergistic chemical modification is performed: firstly, the electrolytic manganese residues are subjected to low-temperature plasma activation pretreatment to increase surface active sites; secondly, carrying out graft copolymerization on lignin in the industrial waste alkali liquor by utilizing an RAFT (Reversible Addition-Fragmentation Chain Transfer) polymerization technology, and introducing carboxyl and amide groups to synthesize a zwitterionic polymer; then, mixing the modified electrolytic manganese residues with modified alkali liquor, and inducing to generate a nano precursor with a core-shell structure through a supramolecular self-assembly and bionic silicification principle; and finally, carrying out spray drying to obtain a final product. According to the mineralizer disclosed by the invention, the grindability and the burnability of cement raw materials can be remarkably improved, the clinker burning coal consumption can be reduced, more importantly, marine cement can be endowed with excellent chloride ion penetration resistance, and meanwhile, high-added-value resource utilization of solid wastes is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of cement admixtures, in particular to a preparation process of an environmentally friendly cement raw material grinding aid mineralizer. BACKGROUND

[0002] Preparation of cement additives from industrial solid waste is a current research hotspot. For example, Chinese invention patent CN119774911A discloses a method for preparing a cement raw material grinding aid mineralizer from electrolytic manganese slag and industrial waste lye. The method prepares a two-component mineralizer through simple mixing, standing, solid-liquid separation and other steps, realizes "waste treatment with waste", and achieves certain energy-saving effect. However, the prior art has a shallow modification degree of solid waste, only utilizes the inherent components in the waste, and fails to create new and higher performance material structures through deep chemical modification. The product has very limited effect on improving the performance of cement, especially on improving the durability indexes such as impermeability and corrosion resistance of marine cement.

[0003] Currently, for marine cement, the technical difficulty lies in how to effectively block the penetration of harmful media such as chloride ions and prevent internal steel corrosion. Conventional mineralizers or grinding aids mainly focus on grinding efficiency and sintering energy consumption, and rarely take into account the fundamental improvement of the microstructure and durability of cement-based materials. In addition, in terms of high-value utilization of solid waste, simple physical mixing or primary chemical reaction has been difficult to meet the needs of high-performance cement materials, and it is urgent to introduce more advanced chemical modification technologies such as controllable polymerization and supramolecular assembly to activate the potential activity of solid waste and directionally construct structures with specific functions.

[0004] Therefore, the present application aims to break through the limitations of the prior art, convert bulk industrial solid waste into a multifunctional cement raw material additive with grinding, mineralization and significant improvement of impermeability performance through the introduction of a series of complex chemical modification processes, not only providing a new solution for energy saving and consumption reduction of the cement industry, but also providing material support for the long-term safety of marine infrastructure. SUMMARY

[0005] The application aims to provide a preparation process of an environmentally friendly cement raw material grinding aid mineralizer. The process uses electrolytic manganese residue and industrial waste lye as raw materials, and the core is a multi-step synergistic chemical modification: first, the electrolytic manganese residue is subjected to low-temperature plasma activation pretreatment to increase the surface active site; second, the lignin in the industrial waste lye is subjected to graft copolymerization by using the RAFT polymerization technology to introduce carboxyl and amide groups and synthesize zwitterionic polymers; then, the modified electrolytic manganese residue and the modified lye are mixed, and through supramolecular self-assembly and biomimetic silicification principles, a nano precursor with a core-shell structure is induced to be generated; finally, the final product is obtained by spray drying. The mineralizer can not only significantly improve the grindability and burnability of the cement raw material, reduce the coal consumption of clinker sintering, but more importantly, can endow marine cement with excellent chloride ion penetration resistance, and at the same time realizes the high-value resource utilization of solid waste.

[0006] A preparation process of an environmentally friendly cement raw material grinding aid mineralizer, comprising the following steps: (1) electrolytic manganese residue pretreatment: electrolytic manganese residue with a water content of 15-40% is placed in a low-temperature plasma reactor, treated under an argon atmosphere at a power of 100-300 W for 5-20 minutes to obtain activated electrolytic manganese residue; (2) graft modification of industrial waste lye: take the industrial waste lye, add 0.5-5% of the RAFT chain transfer agent and 5-20% of the functional monomer based on the dry basis mass of the industrial waste lye to the industrial waste lye, the total amount of the functional monomer is based on the dry basis mass of the industrial waste lye, the functional monomer is a mixture of acrylic acid and N-vinyl formamide, and the controllable free radical polymerization reaction is carried out at 60-80℃ for 2-6 hours to obtain the graft copolymerization modified lye; (3) supramolecular self-assembly and biomimetic silicification: the activated electrolytic manganese residue obtained in step (1) and the graft copolymerization modified lye obtained in step (2) are mixed in a dry basis mass ratio of (1-2):1, and stirred and reacted at 40-60℃ under ultrasonic assistance for 1-4 hours. During the reaction process, the system self-assembles to form a nano composite precursor with manganese oxide as the core and zwitterionic polymer as the shell through hydrogen bonding and electrostatic interaction; (4) post-treatment: the slurry obtained in step (3) is subjected to spray drying, the inlet temperature is 180-220℃, the outlet temperature is 80-100℃, and the powder collected is the environmentally friendly cement raw material grinding aid mineralizer.

[0007] Preferably, the working gas for the low-temperature plasma treatment in step (1) is argon and oxygen mixed gas, and the volume ratio is preferably 9:1, and the treatment pressure is 50-100 Pa.

[0008] Preferably, the RAFT chain transfer agent in step (2) is 2-(dodecylthiothiocarbonylthio)-2-methylpropionic acid; and the molar ratio of acrylic acid to N-vinyl formamide in the functional monomer is (1-3):1.

[0009] Preferably, the controllable radical polymerization reaction in step (2) is carried out in a buffer solution system with a pH of 7-9.

[0010] Preferably, in step (3), the ultrasonic frequency is 40 kHz, and the power density is 50-150 W / L.

[0011] Preferably, in step (3), after the self-assembly reaction is completed, a sodium silicate solution is slowly added to the system, the SiO2 addition amount accounts for 0.5-2% of the total solid content of the system, and the reaction is continued for 0.5-1 hour, so as to further stabilize the nanostructure through biomimetic silicification.

[0012] Preferably, the silicification reacts with Ca(OH)2 to generate additional C-S-H gel during the cement hydration process, fills the capillary pores, optimizes the pore structure, and thus significantly reduces the chloride ion permeability coefficient of the cement stone.

[0013] Preferably, the industrial waste lye is a mixture of papermaking black liquor and saponification waste lye, and the mixing mass ratio is (1-3):1.

[0014] Preferably, in the steps of supramolecular self-assembly and biomimetic silicification, a nano-composite precursor with manganese oxide as the core and zwitterionic polymer as the shell is formed through hydrogen bonding and electrostatic interaction, wherein the carboxyl and amide groups in the zwitterionic polymer are coordinated with Mn 2+ , Ca 2+ ions dissolved from the electrolytic manganese residue, and the polymer chains interact with silicate species on the surface of cement raw material particles through hydrogen bonding, thereby playing the dual functions of molecular bridge and mineralization template during the grinding and calcining processes, so as to improve the grindability, calcinability and clinker impermeability of the cement raw material.

[0015] The mineralization agent prepared in the application is a nano-composite powder with core-shell structure, and the dosage in the cement raw material is 0.5-3.0% of the mass of the raw material.

[0016] The mineralization agent prepared in the application is particularly suitable for the preparation of special low-carbon cement raw materials for marine engineering, can significantly reduce the clinker calcination temperature, and improve the chloride ion permeability of the cement stone.

[0017] Here is a supplement to the average particle size, specific surface area, and carboxyl content measurement method: 1. Average particle size (nanometer level).

[0018] Detection method: dynamic light scattering method (DLS). Instrument: Malvern Zetasizer Nano ZS; Procedure: Take 10 mg sample and disperse in 50 mL deionized water, ultrasonic treatment for 30 minutes; take an appropriate amount of suspension into the sample cell, equilibrate at 25℃ for 2 minutes; set the detection angle to 90°, measure continuously for 3 times, and take the average value as the final particle size result.

[0019] 2. Specific surface area.

[0020] Detection method: BET nitrogen adsorption method; Instrument: Micromeritics ASAP 2460; Procedure: Take 0.2 g sample and vacuum degassing at 150℃ for 4 hours; perform N2 adsorption-desorption test at liquid nitrogen temperature (-196℃); calculate the specific surface area in the relative pressure range of 0.05-0.30 by using the BET model.

[0021] 3. Carboxyl content.

[0022] Detection method: acid-base titration method; Procedure: Accurately weigh 0.5 g sample and disperse in 50 mL 0.01 mol / L NaCl solution; titrate with 0.1 mol / L NaOH solution to pH 8.5, and record the consumption volume V 1 ; continue to back titrate with 0.1 mol / L HCl solution to pH 3.0, and record the consumption volume V 2 ; carboxyl content (mmol / g) calculation formula: Carboxyl content = [ C NaOH * (0.5 g) / (0.5 g x (8.4 - 3.0) x 0.1 mol / L) V 1 - V 2 ] / 2 m 样品 ; Among them, C NaOH = 0.1 mol / L, m 样品 = 0.5 g; The following is the core innovation point of the present application: 1. Precision modification of lignin based on controllable radical polymerization. One of the core innovations of this invention is to graft copolymerize lignin macromolecules in industrial waste lye by using RAFT polymerization, a kind of “living” / controllable polymerization technology. While traditional lye only relies on its inherent surface activity, this invention builds zwitterionic polymer branches on the lignin skeleton by introducing carboxyl groups (from acrylic acid) and amide groups (from N-vinyl formamide) functional monomers. This precise molecular design not only greatly improves the surface activity and dispersibility of the product, but more importantly, its zwitterionic property enables it to interact strongly with various ions in the cement system, laying the foundation for subsequent supramolecular self-assembly.

[0023] 2. Synergistic structure construction of plasma activation and supramolecular self-assembly. Instead of directly using electrolytic manganese residue, this invention first activates it through low-temperature plasma. The high-energy particles in the plasma can effectively clean and etch the surface of manganese residue particles, increasing their surface energy and active sites (such as -OH). When the activated manganese residue is mixed with the RAFT-modified lye, the functional groups in the modified polymer interact strongly with the active sites on the surface of the manganese residue and the dissolved metal ions (Mn 2+ , Ca 2+ ) in solution, spontaneously forming a “core-shell structure” through supramolecular self-assembly. Among them, the inorganic components such as manganese oxides serve as the “core”, while the flexible zwitterionic polymer serves as the “shell”. This structure plays an excellent role in assisting grinding in cement raw material grinding, and as a mineralization template during calcination, guiding the low-temperature formation of clinker minerals.

[0024] 3. Biomimetic silicification strategy to stabilize nanostructure and enhance impermeability. Inspired by the process of biological mineralization in nature (such as diatoms forming siliceous cell walls), this invention introduces sodium silicate during the later stage of self-assembly for biomimetic silicification. The silica precursor undergoes hydrolysis-condensation on the surface of the already formed organic-inorganic nanocomposite structure, forming a thin and stable inorganic silica layer. This process further stabilizes the supramolecular assembly, preventing it from dissociating during subsequent processing. More importantly, when this mineralization agent participates in cement hydration, the active silicon can react with the cement hydration product Ca(OH)2 to generate additional C-S-H gel, effectively filling capillary pores and optimizing pore structure, thereby significantly reducing the permeation rate of chloride ions in cement stone. This is the key mechanism by which the product of this invention can significantly improve the durability of marine cement.

[0025] RAFT polymerization mechanism for graft copolymerization of lignin: Zwitterionic polymer synthesis based on reversible addition-fragmentation chain transfer (RAFT) polymerization, RAFT (Reversible Addition-Fragmentation Chain Transfer) polymerization is a "living" / controlled radical polymerization technique that allows precise control over the length and structure of polymer chains. In this invention, RAFT technology is used to graft copolymerize lignin macromolecules in industrial waste lye, introducing carboxyl groups (from acrylic acid) and amide groups (from N-vinyl formamide) functional monomers to construct zwitterionic polymer branches. This precise molecular design not only greatly improves the surface activity and dispersibility of the product, but more importantly, its zwitterionic properties enable strong interactions with various ions in the cement system, laying the foundation for subsequent supramolecular self-assembly.

[0026] Technical advantages of RAFT polymerization for graft copolymerization of lignin: Compared with traditional radical polymerization, RAFT polymerization can precisely control the length, molecular weight distribution and structure of polymer chains, achieving high molecular design. In this invention, the zwitterionic polymer synthesized by RAFT technology has the following advantages: 1. Precise control of molecular structure to ensure reasonable distribution of carboxyl and amide groups on the polymer chain; 2. Controllable polymer chain length to optimize its dispersibility and surface activity in the cement system; 3. Zwitterionic properties enable strong interactions with various ions in the cement system; 4. Provides structural basis for subsequent supramolecular self-assembly to form stable core-shell structure nanocomposites.

[0027] Mechanism of supramolecular self-assembly to form core-shell structure precursors: Organic-inorganic nanocomposite structure construction based on hydrogen bonding and electrostatic interactions. The mechanism of supramolecular self-assembly is a process of spontaneously forming ordered structures through non-covalent interactions (such as hydrogen bonding, electrostatic interaction, van der Waals force, etc.). In this invention, the active sites on the surface of activated electrolytic manganese slag and the functional groups in the zwitterionic polymer spontaneously assemble into a core-shell structure nanocomposite precursor with manganese oxide as the core and zwitterionic polymer as the shell through hydrogen bonding and electrostatic interaction. This core-shell structure plays an excellent grinding aid role in cement raw material grinding and acts as a mineralization template during calcination, guiding the low-temperature formation of clinker minerals while imparting excellent resistance to chloride ion penetration to cement.

[0028] Technical advantages and mechanism Dual function of core-shell structure: 1. Grinding aid function: The polymer shell layer reduces the surface energy and hardness of particles during cement raw material grinding, improving grinding efficiency.

[0029] 2. Mineralization template: During clinker calcination, the core-shell structure acts as a mineralization template, guiding the low-temperature formation of clinker minerals and reducing the energy consumption of sintering.

[0030] 3. Permeability resistance enhancement: The stable structure formed by biomimetic silicification generates additional C-S-H gel during cement hydration, optimizing the pore structure and significantly improving the resistance to chloride ion penetration.

[0031] This core-shell structure constructed through supramolecular self-assembly realizes the synergistic effect of organic and inorganic components, providing high-performance multifunctional additives for the cement industry.

[0032] The beneficial technical effects of the present application are: 1. Energy saving and consumption reduction with outstanding grinding effect. The mineralizer prepared in the present application can significantly reduce the surface energy and hardness of particles during cement raw material grinding due to its unique core-shell nanostructure and efficient zwitterionic surface activity, thereby increasing the raw material mill output per hour and reducing the power consumption per ton of raw material grinding. During clinker calcination, it acts as a mineralization template to effectively reduce the activation energy of clinker formation, thereby reducing the sintering temperature, lowering the standard coal consumption, significantly improving the qualified rate of free calcium oxide, and achieving significant energy saving and carbon reduction benefits.

[0033] 2. Breakthrough in durability improvement effect. The improvement of marine cement durability by the mineralizer is its most outstanding technical effect. Tests show that the chloride ion diffusion coefficient of marine cement mixed with the mineralizer can be reduced compared to the reference sample, and the sulfate attack resistance is also improved simultaneously. This is mainly due to the stable structure formed by biomimetic silicification, which introduces additional C-S-H gel into the cement paste and optimizes the pore structure, significantly reducing the proportion of harmful pores and forming a more dense microstructure, thereby fundamentally improving the ability of cement-based materials to resist external erosion media.

[0034] 3. Significant solid waste high-value and environmental protection benefits. The present application uses electrolytic manganese residue and industrial waste lye as main raw materials, and realizes the transformation from "waste" to "high-performance materials" through high-tech chemical modification. Each ton of product can consume about 0.7-1.0 tons of dry basis solid waste, and there is no secondary pollution in the production process. Compared with traditional processes using pure chemicals or simply treating solid waste, the present application not only achieves a leap in product performance, but also sets a high-value and fine example in the technical route of solid waste resource utilization, with good environmental and economic benefits. BRIEF DESCRIPTION OF DRAWINGS

[0035] Figure 1 The flow chart for the preparation process of the environmental protection type cement raw material grinding mineralizer of the present application. DETAILED DESCRIPTION

[0036] Before further description of the specific embodiments of the application, it is to be understood that the application is not limited in its application to the specific details set forth in the following description as specific embodiments of the application; and it is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of the present application. The following examples are presented to further illustrate the application, but are not intended to limit the scope of the application.

[0037] When the embodiments give numerical ranges, it is understood that, unless the application indicates otherwise, each numerical range's two endpoints, and any number between the two endpoints, can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. Except in the Examples, or where otherwise explicitly indicated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. As used herein, the singular form "a", "an" and "the" include plural references unless the context clearly dictates otherwise.

[0038] Unless otherwise indicated, the test methods, detection methods, preparation methods disclosed in the application are conventional techniques in the art.

[0039] Limiting conditions of the pulp alkali cooking black liquor: The pulp alkali cooking black liquor described in the application is limited to by-product waste liquid produced by Kraft process or Soda process pulp manufacturing process, to ensure that it contains enough lignin macromolecular skeleton for graft copolymerization; its solid content should be controlled between 20% and 50%, and the lignin (weight average molecular weight 5000-20000 Da) content should not be less than 25% on a dry basis, which is the key to ensure sufficient active sites for subsequent RAFT polymerization; at the same time, the black liquor should be strongly alkaline, with a pH value ranging from 12 to 14, which is both its inherent property and provides the necessary reaction conditions for subsequent polymerization. Through the above clear limitation of source, composition and physicochemical properties, the consistency and reactivity of the raw material are ensured, thereby guaranteeing the stability and reproducibility of the performance of the final product.

[0040] Limiting conditions of the saponification waste lye: The saponification waste lye in the application is specifically defined as by-product lye produced in the industrial production process of propylene oxide, ethylene oxide or fatty acid, to ensure the specificity and consistency of its composition; its effective component is mainly sodium hydroxide, and the mass concentration range should be controlled between 5% and 20%, which can provide sufficient alkaline environment to maintain the pH of the reaction system in cooperation with black liquor, and avoid the occurrence of side reactions caused by excessive alkalinity; the pH value of the waste lye is typically between 13 and 14. By precisely defining its source and concentration, not only the resource utilization of industrial waste liquid is realized, but more importantly, a stable and necessary alkaline reaction medium is provided for the entire preparation process.

[0041] The subsequent examples and comparative examples follow this limitation.

[0042] Example 1 Firstly, the raw material electrolytic manganese residue is pretreated by acid washing: a) Take 600 grams of wet-state electrolytic manganese residue (because of its water content, after subsequent drying and treatment, about 500 grams of wet residue is finally used for the main reaction, with a water content of 25%), and mix it with 1.5 mol / L dilute sulfuric acid at a solid-liquid mass ratio of 1:5, and mechanically stir at 60°C for 1 hour; b) After the reaction is completed, vacuum filtration is performed, and the filter residue is repeatedly washed with deionized water until the pH of the filtrate is about 6.0 detected using pH paper; c) The washed filter residue is placed in a 105°C oven to dry to constant weight, and then deionized water is added to adjust the water content to 25%, obtaining the acid-washed electrolytic manganese residue, 500 grams of which is taken for standby use.

[0043] Next, plasma activation is performed: Take the above-mentioned 500 grams of acid-washed electrolytic manganese residue (water content 25%) and place it in the reaction cavity of a low-temperature plasma treatment instrument. After vacuumizing to a system pressure of 100 Pa, a mixed gas of argon and oxygen with a volume ratio of 9:1 is introduced as the working gas, the plasma emission power is set to 200 W, and the manganese residue is activated for 10 minutes to obtain activated electrolytic manganese residue for standby use.

[0044] Next, the industrial waste lye is grafted and copolymerized: take the paper pulp alkali cooking black liquor (sulfate method (Kraft method) pulping black liquor, solid content 35%, dry basis lignin content 30%, lignin number average molecular weight (Mn) 8000 Da, pH value 13.2, ash content 15%, hemicellulose content 8%) and saponification waste lye (propylene oxide production by-product lye, sodium hydroxide mass concentration 12%, pH value 13.8, Cl⁻ content 0.5%, SO4 2-The industrial waste lye was mixed with 300 g of the graft copolymerization modified lye (calculated on the basis of dry mass) in a 1000 ml three-necked flask equipped with a mechanical stirrer, a condenser and a nitrogen inlet. 1.5 g of the chain transfer agent, 15 g of acrylic acid and 10 g of N-vinyl formamide were added as functional monomers. The pH value of the system was adjusted to 8.0 with a dilute sodium hydroxide solution. After the system was purged with nitrogen to remove air, the reaction system was placed in a 70°C constant temperature oil bath and stirred at a speed of 200 rpm for 4 hours of RAFT controlled radical polymerization. A brownish viscous graft copolymerization modified lye was obtained after the reaction. Then, supramolecular self-assembly and biomimetic silicification were carried out. The activated electrolytic manganese residue and the graft copolymerization modified lye (dry mass ratio of about 1.5:1) were added to a 2000 ml beaker, which was placed in an ultrasonic cleaner (ultrasonic frequency of 40 kHz and power density of 100 W / L) in a water tank. The system was mechanically stirred at a speed of 300 rpm for 2 hours in a 50°C constant temperature water bath and under ultrasonic field to promote the self-assembly of organic and inorganic components through supramolecular interaction. Then, a constant pressure dropping funnel was used to slowly add a prepared sodium silicate aqueous solution (containing 1% of SiO2 by mass based on the total solid dry mass of the system) into the system. After the addition was completed, the reaction was continued for 0.5 hours under the same conditions to complete the biomimetic silicification process. Finally, the obtained reaction slurry was dried and shaped, the inlet air temperature was controlled at 200°C, the outlet air temperature was controlled at 90°C, the atomizer speed was controlled at 20000 rpm, and the fine powder collected in the cyclone separator was the final product of this example, marked as P1.

[0045] Example 2 The raw electrolytic manganese residue was pretreated by acid washing, and then plasma activated. 500 g of the acid-washed electrolytic manganese residue (water content of 25%) was placed in the reaction cavity of a low-temperature plasma treatment instrument. After the system was vacuumed to a pressure of 100 Pa, a mixture of argon and oxygen gases with a volume ratio of 9:1 was introduced as the working gas. The electrolytic manganese residue was activated for 10 minutes at a plasma emission power of 150 W to obtain activated electrolytic manganese residue for standby use.

[0046] Next, the modification of the industrial waste lye was performed: 300 grams (dry basis) of mixed industrial waste lye from the same source and with the same composition as in Example 1 was placed in the same reaction device, and 1.5 grams of the same RAFT chain transfer agent was added, but only 25 grams of acrylic acid was used as the functional monomer component, and no N-vinyl formamide was used. The RAFT polymerization reaction was performed under the same conditions of pH = 8.0, 70°C, and nitrogen protection for 4 hours to obtain the modified lye. Then, the mixing and self-assembly were performed: the entire activated manganese slag was mixed with the entire modified lye (the dry basis mass ratio was still 1.5:1), and the reaction was stirred under the same ultrasonic assistance (power density 100 watts per liter) and at 50°C for 2 hours. It is worth noting that this example omitted the step of adding sodium silicate to perform biomimetic silicification after the self-assembly reaction was completed. Finally, the obtained slurry was dried under the same spray drying conditions (inlet air temperature 200°C, outlet air temperature 90°C) as in Example 1, and the obtained powder was collected, which was the final product of this example, labeled as P2.

[0047] Example 3 First, the plasma activation treatment step of the acid-washed and pretreated electrolytic manganese slag was exactly the same as in Example 1, i.e., 500 grams of wet manganese slag was treated under the conditions of 200 watts of power, Ar / O2 mixed gas, 100 Pa pressure, and for 10 minutes. Next, the RAFT graft copolymerization modification step of the industrial waste lye was also exactly the same as in Example 1, using the same RAFT chain transfer agent and mixed monomers of acrylic acid and N-vinyl formamide, and the reaction was performed under the same conditions for 4 hours to prepare the graft copolymerization modified lye. Then, the supramolecular self-assembly was performed: the entire activated electrolytic manganese slag was mixed with the entire graft copolymerization modified lye, but the dry basis mass ratio of the two was adjusted to 1:1, and then the reaction was stirred under the same ultrasonic assistance (50°C, power density 100 watts per liter) for 2 hours. Subsequently, the biomimetic silicification treatment was performed: a sodium silicate aqueous solution was slowly added to the assembled system, but the amount of SiO2 added was increased to 2% of the total solid dry basis mass of the system, and the reaction was continued under the same conditions for 0.5 hours. Finally, the final slurry was dried and granulated using the same spray drying parameters (inlet air temperature 200°C, outlet air temperature 90°C) as in Example 1, and the obtained powder product was collected, which was labeled as P3.

[0048] Example 4 This example aims to investigate the applicability of the dry electrolytic manganese residue after long-term storage. First, the electrolytic manganese residue after long-term storage and natural air drying (measured moisture content less than 5%) was taken, 375 grams of dry residue was weighed, and then 125 grams of deionized water was added, mechanically stirred for 30 minutes, and then re-conditioned into a uniform slurry with a moisture content of about 25% to simulate the physical state of wet residue. Subsequently, acid washing pretreatment (this step is consistent with Example 1), and then the reconstituted manganese residue slurry undergoes the same plasma activation treatment process as Example 1 (200 watts, Ar / O2, 100 Pa, 10 minutes). The RAFT grafting copolymerization modification step of industrial waste lye is strictly the same as Example 1. Then, the activated reconstituted manganese residue and the modified lye are mixed at a dry basis mass ratio of 1.5:1, and the supramolecular self-assembly reaction is carried out under the same conditions as Example 1 (50°C, ultrasonic power density 100 watts / liter) for 2 hours. After self-assembly is completed, the same biomimetic silicification step as Example 1 is performed, i.e., adding 1% of SiO2 (from sodium silicate solution) based on the total solid content of the system, and continuing to react for 0.5 hours. Finally, the treated slurry is dried under the same spray drying conditions as Example 1 (inlet air 200°C, outlet air 90°C), and the collected powder product is labeled as P4.

[0049] Example 5 First, the electrolytic manganese residue is acid washed and pretreated (this step is consistent with Example 1), and then the plasma activation pretreatment step is exactly the same as Example 1. Then, the deep grafting copolymerization modification of industrial waste lye is carried out: 300 grams (dry basis) of mixed industrial waste lye of the same source and ratio as Example 1 is taken and placed in the reaction device, 1.5 grams of the same mass of RAFT chain transfer agent is added, but the composition and ratio of the functional monomers are adjusted, the amount of acrylic acid is increased to 22.5 grams, and the amount of N-vinyl formamide is reduced to 7.5 grams (so that the molar ratio of the two is about 3:1), the reaction conditions are still pH=8.0 and 70°C, but the RAFT polymerization reaction time is extended to 6 hours in order to obtain a higher grafting rate and a more regular polymer chain structure. Then, all the activated manganese residue and the lye obtained by this deep modification are mixed at a dry basis mass ratio of 1.5:1, and the supramolecular self-assembly reaction is carried out under the same conditions as Example 1 (50°C, ultrasonic power density 100 watts / liter) for 2 hours. After self-assembly is completed, the same biomimetic silicification step as Example 1 is performed, i.e., adding 1% of SiO2 based on the total solid content of the system, and continuing to react for 0.5 hours. Finally, the final slurry is dried under the same spray drying parameters as Example 1 (inlet air 200°C, outlet air 90°C), and the collected powder is the final product of this example, labeled as P5.

[0050] Comparative Example 1 The comparative example is strictly carried out according to the method of Example 1 of the reference Chinese invention patent CN119774911A: at room temperature, wet-state electrolytic manganese residue (moisture content 25%) and unmodified mixed industrial waste lye (pulp black liquor and saponified waste lye mixed at a dry basis of 2:1) are placed in a sealed container at a dry basis mass ratio of 1.5:1, and the exhaust port of the container is connected to dilute sulfuric acid absorption liquid to recover possible volatile ammonia gas; after the mixture is uniformly stirred into a slurry using a mechanical stirrer, it is left to stand for 3 hours under a sealed condition; after standing, the slurry is subjected to solid-liquid separation using a vacuum filtration device, and the filter cake part is collected; the obtained filter cake is dried in a 105°C oven to constant weight, and then crushed and ground to a certain fineness to obtain the mineralizer product of the comparative example, labeled as D1. This process does not involve any deep chemical modification steps such as plasma activation, RAFT polymerization, supramolecular self-assembly, and biomimetic silicification.

[0051] Comparative Example 2 The comparative example aims to investigate the difference between RAFT polymerization and conventional free radical polymerization: the preparation process is generally similar to Example 1, but in the key step of industrial waste lye modification, instead of using a RAFT chain transfer agent, a traditional ammonium persulfate (APS) is used as an initiator for free radical graft copolymerization. Specifically, take the same mass (300 grams dry basis) and ratio of mixed industrial waste lye as Example 1, add 3% ammonium persulfate based on the total mass of monomers, and the same mass of acrylic acid and N-vinyl formamide mixed monomers (total amount 25 grams, molar ratio same as Example 1), react at 70°C, pH=8.0 for 4 hours to obtain a conventionally polymerized modified lye. The subsequent steps, including mixing with plasma-activated manganese residue (conditions same as Example 1), ultrasonic-assisted reaction, biomimetic silicification treatment, and spray drying, are all consistent with the operating parameters of Example 1, and finally the product is labeled as D2.

[0052] Comparative Example 3 The comparative example aims to investigate the importance of plasma activation pretreatment: the preparation process is similar to Example 1, but the plasma activation treatment step of the electrolytic manganese residue is completely omitted. Specifically, directly take 500 grams of original wet-state electrolytic manganese residue (without any plasma treatment), and mix it with the RAFT graft copolymerized modified industrial waste lye (its preparation method is exactly the same as Example 1) at a dry basis mass ratio of 1.5:1. The subsequent steps of ultrasonic-assisted self-assembly reaction, biomimetic silicification treatment (adding 1% SiO2), and spray drying forming are all strictly followed the process conditions and parameters of Example 1, and finally the product is labeled as D3.

[0053] Comparative Example 4 This comparative example aims to investigate the synergistic effect of supramolecular self-assembly and biomimetic silication steps: in its preparation process, the key processes of supramolecular self-assembly and biomimetic silication are omitted. Specifically: first, according to the same method of Example 1, plasma-activated electrolytic manganese slag and RAFT graft copolymerization modified industrial waste lye are prepared; then, the two are simply physically mixed in a beaker at a dry basis mass ratio of 1.5:1, mixed under ordinary mechanical stirring (300 rpm, 50°C) for 1 hour, without applying an ultrasonic field, and without subsequent dropwise addition of sodium silicate reaction; finally, the slurry after simple mixing is directly dried under the same spray drying conditions as Example 1, and the collected powder is the product of this comparative example, labeled as D4.

[0054] Comparative Example 5 This comparative example uses a commercially available conventional mineralizer as a performance reference benchmark. The specific implementation details are: directly purchase a commercially available composite mineralizer widely used in cement production, whose main components are calcium fluoride (CaF2) and gypsum dihydrate (CaSO4·2H2O), and use it according to the product instructions by directly adding it to the raw material batching as an external additive. In this series of comparative tests, the commercially available mineralizer is labeled as D5, and its test results are compared with those of each embodiment and comparative example of the present application to directly show the performance advantages brought by the technical solutions of the present application.

[0055] Performance Test Test method: refer to the comparative document CN119774911A and the corresponding national standard, and test under an industrial test scale. The main detection parameters include: mill output, ton of raw material grinding power consumption, clinker daily output, kiln inlet raw material decomposition rate, decomposition furnace outlet temperature, clinker calcination standard coal consumption, clinker free lime pass rate, and compressive strength of each age. At the same time, in order to characterize the characteristics of marine cement, the chloride ion permeability coefficient of cement mortar test body (tested according to the RCM method) is also measured.

[0056] Table 1 Comparison of the use effects of the grinding aid mineralizers of each embodiment

[0057] Table 2 Comparison of the use effects of the grinding aid mineralizers of each comparative example

[0058] According to the above Tables 1 and 2, it can be seen that: Reasons for the differences in the test results of Examples 1-5: The performance difference of Examples 1-5 mainly comes from the subtle changes in process parameters. Examples 1, 3, 5 adopt the complete modification steps (including biomimetic siliconization), while Example 2 omits siliconization, resulting in a higher chloride ion permeability coefficient, because siliconization can stabilize the nanostructure and generate C-S-H gel to fill the pores. Example 5 obtains more regular polymer chains by extending the polymerization time and adjusting the monomer ratio (molar ratio 3:1), thereby optimizing the core-shell structure, showing the best performance. Example 3 uses a 1:1 dry basis mass ratio, and the self-assembly effect is slightly weaker than 1.5:1, but is still within a reasonable range. Example 4 uses reconstituted manganese slag, with slightly lower activity, slightly poorer performance but close to Example 1. Overall, the complete chemical modification, optimized parameters (such as power, ratio), and siliconization treatment synergistically enhance the grinding aid, mineralization, and impermeability performance.

[0059] The difference between the example and Comparative Example 1 mainly comes from the modification depth: Comparative Example 1 uses the simple mixing method of the prior art, without plasma activation, RAFT polymerization, self-assembly, and siliconization, only utilizing the inherent ingredients of solid waste, lacking nanostructure and zwitterionic polymer function. Therefore, its product cannot form "molecular bridge" and "mineralization template", resulting in poor grinding aid effect, high coal consumption, low qualified rate of free calcium oxide, and weak resistance to chloride ion permeation. The present application activates the activity of solid waste through deep modification and constructs a core-shell structure, while Comparative Example 1 only realizes the primary "waste treatment with waste", with limited performance improvement.

[0060] The difference between the example and Comparative Example 2 lies in the polymerization technology: Comparative Example 2 uses traditional free radical polymerization (APS initiator) instead of RAFT controlled polymerization, resulting in irregular polymer chain structure and low grafting efficiency, affecting the uniformity of zwitterionic polymer and self-assembly effect. Therefore, its core-shell structure is not perfect, the grinding aid and mineralization effect are weakened, and the impermeability is poor. RAFT polymerization can precisely control the chain length and functional group distribution, ensuring effective coordination of the polymer with manganese slag ions, while the random polymerization of Comparative Example 2 cannot achieve such synergistic effect.

[0061] The difference between the example and Comparative Example 3 comes from the absence of plasma activation: Comparative Example 3 omits this step and directly uses the original manganese slag, which has fewer active sites on the surface and weaker interaction with the modified polymer, resulting in insufficient self-assembly and incomplete formation of the core-shell structure. Therefore, the grinding aid effect is reduced, the coal consumption is high, and the impermeability is poor. Plasma activation increases the surface energy and functional groups through high-energy particle bombardment, which is the key to enhancing the organic-inorganic interface bonding.

[0062] The difference between the embodiment and Comparative Example 4 lies in the omission of self-assembly and siliconization: Comparative Example 4 is only simply mixed, without applying an ultrasonic field and siliconization, and cannot form an ordered core-shell structure, resulting in the product lacking the function of "molecular bridge" and stability. Therefore, although the grinding aid effect is improved to a certain extent (due to the modified components), the mineralization and anti-permeability performance are significantly insufficient. Supramolecular self-assembly constructs nanometer precursors through hydrogen bonding and electrostatic interaction, and biomimetic siliconization further stabilizes the structure and optimizes the pore structure. The simple mixing of Comparative Example 4 cannot achieve these mechanisms.

[0063] The difference between the embodiment and Comparative Example 5 is derived from the functional design of the product: Comparative Example 5 uses commercially available conventional mineralizers (CaF2 and gypsum), which mainly provide mineralization, but lack grinding aid and anti-permeability functions. Therefore, its performance is close to the blank sample, and even worse, because commercially available products cannot form a core-shell structure or introduce zwitterionic polymers. The product of the present application realizes multifunctional integration (grinding aid, mineralization, anti-permeability) through multi-step modification, while Comparative Example 5 only targets traditional mineralization and cannot meet the high durability requirements of marine cement.

[0064] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of the present application and not to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present application.

Claims

1. A process for the preparation of an eco-friendly cement raw meal grinding aid mineralizer, characterized by, The method comprises the following steps: (1) electrolytic manganese residue pretreatment: electrolytic manganese residue with a water content of 15-40% is placed in a low-temperature plasma reactor, treated under an argon atmosphere at a power of 100-300 W for 5-20 minutes to obtain activated electrolytic manganese residue; (2) industrial waste lye grafting modification: industrial waste lye is taken, 0.5-5% of the RAFT chain transfer agent and 5-20% of the functional monomer based on the dry mass of the industrial waste lye are added to the industrial waste lye, the total amount of the functional monomer is based on the dry mass of the industrial waste lye, the functional monomer is a mixture of acrylic acid and N-vinyl formamide, and a controllable free radical polymerization reaction is carried out at 60-80 ℃ for 2-6 hours to obtain a graft copolymerized modified lye; (3) supramolecular self-assembly and biomimetic silicification: the activated electrolytic manganese residue obtained in step (1) and the graft copolymerized modified lye obtained in step (2) are mixed in a dry mass ratio of (1-2):1, and stirred and reacted at 40-60 ℃ under ultrasonic assistance for 1-4 hours, during the reaction process, the system is self-assembled through hydrogen bonding and electrostatic interaction to form a nano-composite precursor with manganese oxide as the core and zwitterionic polymer as the shell; (4) post-treatment: the slurry obtained in step (3) is subjected to spray drying, the inlet temperature is 180-220 ℃, the outlet temperature is 80-100 ℃, and the collected powder is the raw cement grinding aid mineralizer.

2. The process for the preparation of eco-friendly cement raw meal grinding aid mineralizer as claimed in claim 1, wherein the process comprises of the steps of: In step (1), the working gas for the low-temperature plasma treatment is a mixture of argon and oxygen, the volume ratio is 9:1, and the treatment pressure is 50-100 Pa.

3. The process for the preparation of eco-friendly cement raw meal grinding aid mineralizer as claimed in claim 1 wherein, Before the electrolytic manganese residue pretreatment in step (1), the electrolytic manganese residue is also subjected to acid pickling pretreatment, and the acid pickling pretreatment comprises: ​ a) electrolytic manganese residue is mixed with 1-3 mol / L dilute sulfuric acid at a solid-liquid mass ratio of 1:5, stirred at 50-70 ℃ for 0.5-2 hours; b) filtration, and washing the filter residue with deionized water until the pH of the filtrate is 5.5-6.5; c) drying the washed filter residue to a water content of 15%-40% to obtain acid-pickled electrolytic manganese residue for the plasma activation treatment in step (1).

4. The preparation process of the environmentally friendly cement raw meal grinding aid mineralizer according to claim 1, characterized in that: In step (2), the RAFT chain transfer agent is 2-(dodecylsulfanylthiocarbonylthio)-2-methylpropanoic acid; the molar ratio of acrylic acid to N-vinyl formamide in the functional monomer is (1-3):1; and the controllable free radical polymerization reaction is carried out in a buffer solution system with a pH of 7-9.

5. The preparation process of the environmentally friendly cement raw meal grinding aid mineralizer according to claim 1, characterized in that: In step (3), the ultrasonic frequency is 40 kHz, and the power density is 50-150 W / L.

6. The process for the preparation of eco-friendly cement raw meal grinding aid mineralizer as claimed in claim 1, wherein the process comprises of the steps of: In step (3), after the self-assembly reaction is completed, a sodium silicate solution is slowly added to the system, the SiO2 addition amount accounts for 0.5-2% of the total solid content of the system, and the reaction is continued for 0.5-1 hour to further stabilize the nanostructure through biomimetic silicification.

7. The preparation process of the environmentally friendly cement raw meal grinding aid mineralizer according to claim 6, characterized in that: The silicification reacts with Ca(OH)2 to generate additional C-S-H gel during the cement hydration process, fills the capillary pores, optimizes the pore structure, and significantly reduces the chloride ion permeability coefficient of the cement stone.

8. The preparation process of the environmentally friendly cement raw meal grinding aid mineralizer according to claim 1, characterized in that: The industrial waste lye is a mixture of papermaking black liquor and saponified waste lye, and the mixing mass ratio is (1-3):

1.

9. The process for the preparation of an eco-friendly cement raw meal grinding aid mineralizer as claimed in claim 1, wherein the process is characterized by: In the supermolecular self-assembly and biomimetic silicification step, a nanocomposite precursor with manganese oxide as the core and zwitterionic polymer as the shell is formed through hydrogen bonding and electrostatic interaction; wherein the carboxyl and amide groups in the zwitterionic polymer interact with the Mn 2+ , Ca 2+ ions dissolved from the electrolytic manganese residue through plasma coordination, and the polymer chains interact with silicate species on the surface of cement raw material particles through hydrogen bonding, thereby playing the dual functions of molecular bridge and mineralization template in the grinding and calcination processes, so as to improve the grindability, calcinability and clinker impermeability of the cement raw material.

10. A cement raw meal grinding mineralizer prepared according to the process of any one of claims 1-9, characterized in that: The mineralizer is a nano-composite powder with core-shell structure, and the mixing amount of the nano-composite powder in the cement raw material is 0.5-3.0% of the mass of the raw material; the average particle size of the nano-composite powder is 50-200nm, the specific surface area is ≥50m² / g, and the carboxyl content is ≥0.5mmol / g.

Citation Information

Patent Citations

  • Preparation method and application of environment-friendly cement raw material grinding-aid grinding agent

    CN119774911A

Cited By

  • Early-strength belite sulphoaluminate cement clinker and preparation method thereof

    CN122212516A